FOSM-based shear reliability analysis of CSGR dams using strength theory. (May 2018) - Jia, Jinsheng; Wang, Sha; Zheng, Cuiying; Chen, Zuping; Wang, Yang
Abstract: The cemented sand, gravel and rock (CGSR) dam is a new type of dam that combines the characteristics of a rigid dam and an embankment dam. Mechanical tests show that the shear strength of CSGR is much lower than that of concrete and present significant discreteness; shear failure of a CSGR dam is more similar to a failure in material than a failure along the contact between two materials and is quite different from the failure of a rigid dam. The rigid equilibrium method (REM), which adopts the parameters φ and C, could cause great calculation error when applied to the stability evaluation of a CSGR dam. Because of the uncertainty of the shearing parameters, reliability theory should be used to analyze the shearing stability of CSGR dams. In this study, shear criteria based on the theories of Mohr Coulomb and double-shear strength failure and the corresponding limit state equations using uniaxial compressive and tensile strength as random variables are proposed to evaluate the shearing stability of CSGR dams; then, the reliability index of above limit state equations is solved using the reliability method of first-order second moment (FOSM) combined with the finite element method; the failure probability can thus be evaluated on a local scale. The FOSM-based method proposed in this study is applied to the case study of Shou Koubao Dam. The conclusions drawn from the results will contribute to the risk analysis of CSGR dams in the future.